Pengaruh Diabetes Self Management Education And Support (DSME/S) Terhadap Peningkatan Pengetahuan Manajemen Mandiri Pasien Dm Tipe 2 - Yuni, Chairunnisa Mei; Diani, Noor; Rizany, Ichsan (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Diabetes mellitus (DM) is a chronic complex disease that requires medical care, self managementeducation and ongoing support to prevent complications. Health education is one of steps toincrease knowledge and skills of diabetes management independently to avoid the complication ofDM, one of them is Diabetes Self Management Education and Support (DSME/S). The aim of thisstudy was to determine the effect of DSME/S on increasing the independent management ofknowledge of patients with type 2 DM. This study use pre experimental method with one grouppretest-posttest design. There were 30 patients with type 2 DM at Idaman Kota BanjarbaruHospital on March-April 2018. This study used consecutive sampling technique. Follow up wasconducted after intervention on the third day. The instruments were module, demographicquestionnaire and DM knowledge questionnaire. Based on Paired t test results, there is an effect ofDSME/S on increasing the independent management ofknowledge of patients with type 2 DM was0.0001 (p<α; α=0.005), with an increase of 15.97%. DSME/S is effective on improving knowledgeof patient with type 2 DM, so it can be given to patients with type 2 DM as self-managementeducation to prevent complications.